Association study between immune-related miRNAs and mixed connective tissue disease - Barbara Stypińska; Aleksandra Lewandowska; Anna Felis-Giemza; Marzena Olesińska; Agnieszka Paradowska-Gorycka (Arthritis Research & Therapy, 2021)
Abstract Background Mixed connective tissue disease (MCTD) is a rare condition that is distinguished by the presence of specific U1-RNP antibodies. Information about its etiopathology and diagnostics is still unclear. miRNAs such as miR-146, miR-155, and miR-143 emerged as key regulators of the immune system, known to be involved in the development of autoimmune diseases and cancers. We performed an association study between immune-related miRNAs and MCTD severity and susceptibility. Methods A total of 169 MCTD patients and 575 healthy subjects were recruited to the case–control study. The miRNA polymorphisms were genotyped using TaqMan SNP genotyping assay. TNF-α, IL-6, and IFN-γ levels in serum were determined using ELISA. qRT-PCR of TRAF6, IRAK1, and microRNAs was performed using Taqman miRNA assays and TaqMan Gene Expression Assays. Results miR-146a rs2910164 G allele and GG genotype as well as miR-143 rs713147 A allele were more frequent in healthy subjects than in MCTD patients. miR-146a rs2910164 CC genotype and miR-143 T-rs353299*T-rs353291*T-rs713147*G-rs353298 and C-rs353299*C-rs353291*T-rs713147*A-rs353298 haplotypes were associated with MCTD susceptibility. miR-146a rs2910164 C/T was associated with scleroderma and lymphadenopathy. miR-143 rs353299 C/T was associated with swollen fingers or hands, the presence of enlarged lymph nodes, and pericarditis/pleuritis. miR-143 rs353298 A/G was associated with the occurrence of pericarditis/pleuritis and scleroderma. miR-143 rs353291 T/C showed association with pericarditis/pleuritis. The serum TNF-α, IFN-γ, and IL-6 levels were significantly higher in MCTD patients compared to healthy subjects. miR-143 SNPs were associated with higher proinflammatory cytokine concentration in serum only in healthy controls. IRAK1 and TRAF6 expression were higher in the MCTD patients compared to controls. Conclusions The results of our case–control study indicate the possible significance of miR-146a and miR-143/145 in the susceptibility and clinical picture of MCTD.